Isolation and Differentiation of Neurons and Glial Cells from Olfactory Epithelium in Living Subjects - Paula Unzueta-Larrinaga; Rocío Barrena-Barbadillo; Inés Ibarra-Lecue; Igor Horrillo; Aitor Villate; Maria Recio; J. Javier Meana; Rebeca Diez-Alarcia; Oihane Mentxaka; Rafael Segarra; Nestor Etxebarria; Luis F. Callado; et al. (Molecular Neurobiology, 2023)
The study of psychiatric and neurological diseases requires the substrate in which the disorders occur, that is, the nervous tissue. Currently, several types of human bio-specimens are being used for research, including postmortem brains, cerebrospinal fluid, induced pluripotent stem (iPS) cells, and induced neuronal (iN) cells. However, these samples are far from providing a useful predictive, diagnostic, or prognostic biomarker. The olfactory epithelium is a region close to the brain that has received increased interest as a research tool for the study of brain mechanisms in complex neuropsychiatric and neurological diseases. The olfactory sensory neurons are replaced by neurogenesis throughout adult life from stem cells on the basement membrane. These stem cells are multipotent and can be propagated in neurospheres, proliferated in vitro and differentiated into multiple cell types including neurons and glia. For all these reasons, olfactory epithelium provides a unique resource for investigating neuronal molecular markers of neuropsychiatric and neurological diseases. Here, we describe the isolation and culture of human differentiated neurons and glial cells from olfactory epithelium of living subjects by an easy and non-invasive exfoliation method that may serve as a useful tool for the research in brain diseases.

Altitudinal distribution of the entire invasive small mammal guild in the eastern dryland zone of New Zealand’s Southern Alps - Nicholas J. Foster; Richard F. Maloney; Philip J. Seddon; Mariano R. Recio; Md Saiful I. Khan; Yolanda van Heezik (Biological Invasions, 2021)

Application of low-density electric current to performance improvement of membrane bioreactor treating raw municipal wastewater - A. A. Battistelli; T. J. Belli; R. E. Costa; N. M. Justino; D. D. Silveira; M. A. Lobo-Recio; F. R. Lapolli (International Journal of Environmental Science and Technology, 2019)

Correlation between in vitro and in vivo data on food digestion. What can we predict with static in vitro digestion models? - T. Bohn; F. Carriere; L. Day; A. Deglaire; L. Egger; D. Freitas; M. Golding; S. Le Feunteun; A. Macierzanka; O. Menard; B. Miralles; A. Moscovici; et al. (Critical Reviews in Food Science and Nutrition, 2018)

Seasonal and latitudinal variation in seagrass mechanical traits across Europe: The influence of local nutrient status and morphometric plasticity - L. M. Soissons; M. M. van Katwijk; G. Peralta; F. G. Brun; P. G. Cardoso; T. F. Grilo; B. Ondiviela; M. Recio; M. Valle; J. M. Garmendia; F. Ganthy; I. Auby; et al. (Limnology and Oceanography, 2018)
Seagrasses are marine flowering plants distributed worldwide. They are however threatened, mostly due to the increase of human activities. Seagrasses have the capacity to adapt their morphological, physiological, and mechanical traits to their local conditions. Mechanical traits have been identified as a good tool to investigate a plant‐species capacity to withstand physical forces or disturbances but are still sparsely studied in seagrasses. With this study, we aimed to assess how the mechanical traits of a broadly spread seagrass species vary along a latitudinal gradient in relation to its morphometric plasticity and nutrient status. We found that seagrasses acclimate their mechanical traits in relation to their physiological or morphological traits, both over the growing season and across a latitudinal range: leaves were weaker and thinner in northern areas, particularly at the end of the growing season. Besides the influence of the latitudinal gradient, leaf mechanical strength and stiffness were both strongly affected by their morphometric plasticity. Moreover, we showed that leaves mechanical traits change depending on their nutrient status: leaves were stronger and stiffer in oligotrophic conditions as compared to more eutrophic conditions. Thus, our results imply that, under eutrophication, leaves become weaker and thus more vulnerable to physical forces. This vulnerability is higher in the north at the end of the growing season. The latter is consistent with the more ephemeral character of northern seagrass meadows, in contrast to the more evergreen southern meadows.

Optimizing control programmes by integrating data from fine-scale space use by introduced predators - Mariano R. Recio; Richard F. Maloney; Renaud Mathieu; Emilio Virgós; Antoni B. Moore; Philip J. Seddon (Biological Invasions, 2017)

Pollen limitation may be a common Allee effect in marine hydrophilous plants: implications for decline and recovery in seagrasses - B. I. Van Tussenbroek; L. M. Soissons; T. J. Bouma; R. Asmus; I. Auby; F. G. Brun; P. G. Cardoso; N. Desroy; J. Fournier; F. Ganthy; J. M. Garmendia; L. Godet; et al. (Oecologia, 2016)

Adsorption of chromium(VI) onto electrochemically obtained magnetite nanoparticles - L. J. Martínez; A. Muñoz-Bonilla; E. Mazario; F. J. Recio; F. J. Palomares; P. Herrasti (International Journal of Environmental Science and Technology, 2015)

Longitudinal evaluation of hepatitis C viral persistence in HIV-infected patients with spontaneous hepatitis C clearance - A. Rivero-Juarez; A. Caruz; L. M. Real; L. Martinez-Dueñas; F. J. Marquez; M. Frias; E. Recio; A. Gordon; J. A. Pineda; A. Rivero; A. Camacho (European Journal of Clinical Microbiology & Infectious Diseases, 2015)